Template-Free Synthesis of Sb2S3 Hollow Microspheres as Anode Materials for Lithium-Ion and Sodium-Ion Batteries - Xie, Jianjun; Liu, Li; Xia, Jing; Zhang, Yue; Li, Min; Ouyang, Yan; Nie, Su; Wang, Xianyou (Nano-Micro Letters, 2017)
Hierarchical Sb2S3 hollow microspheres assembled by nanowires have been successfully synthesized by a simple and practical hydrothermal reaction. The possible formation process of this architecture was investigated by X-ray diffraction, focused-ion beam-scanning electron microscopy dual-beam system, and transmission electron microscopy. When used as the anode material for lithium-ion batteries, Sb2S3 hollow microspheres manifest excellent rate property and enhanced lithium-storage capability and can deliver a discharge capacity of 674 mAh g−1 at a current density of 200 mA g−1 after 50 cycles. Even at a high current density of 5000 mA g−1, a discharge capacity of 541 mAh g−1 is achieved. Sb2S3 hollow microspheres also display a prominent sodium-storage capacity and maintain a reversible discharge capacity of 384 mAh g−1 at a current density of 200 mA g−1 after 50 cycles. The remarkable lithium/sodium-storage property may be attributed to the synergetic effect of its nanometer size and three-dimensional hierarchical architecture, and the outstanding stability property is attributed to the sufficient interior void space, which can buffer the volume expansion. Highlights: 1 Sb2S3 hollow microspheres have been successfully synthesized by a simple hydrothermal reaction using SbCl3 and l-cysteine as raw materials without adding any surfactants. 2 The novel architecture combines the merits of nanometer size, hollow interior, and 3D hierarchical structure. 3 The material presents remarkable cycling performance and outstanding rate capability in lithium-ion batteries and also exhibits superior sodium-storage capabilities in sodium-ion batteries.